2021
DOI: 10.1002/brb3.2162
|View full text |Cite
|
Sign up to set email alerts
|

On the processing of optimal performances: Studying arousal evoked by being correct and fast

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In paragraph 5.1 we discussed cognitive changes of patients SCI ≥ T6 on tasks indirectly relying on processing speed (e.g., Dowler et al, 1995), response inhibition and sustained attention when feedback is provided (Davidoff et al, 1985). These findings suggest that phasic physiological arousal evoked on a trial by trial basis during cognitive tasks -e.g., by response feedback (Valt and Stürmer, 2021) -cannot guide optimal performance. We pose that arousal and motivation play an important role in resolving emotional conflict in SCI.…”
Section: The Loss Of Physiological Arousal and Its Effects On Emotion...mentioning
confidence: 99%
See 1 more Smart Citation
“…In paragraph 5.1 we discussed cognitive changes of patients SCI ≥ T6 on tasks indirectly relying on processing speed (e.g., Dowler et al, 1995), response inhibition and sustained attention when feedback is provided (Davidoff et al, 1985). These findings suggest that phasic physiological arousal evoked on a trial by trial basis during cognitive tasks -e.g., by response feedback (Valt and Stürmer, 2021) -cannot guide optimal performance. We pose that arousal and motivation play an important role in resolving emotional conflict in SCI.…”
Section: The Loss Of Physiological Arousal and Its Effects On Emotion...mentioning
confidence: 99%
“…Although this relationship has been predicted for tonic arousal, there is evidence that internal signals of moment by moment changes in arousal affect brain processing and cognitive control. For instance, Valt and Stürmer (2021) showed that enhanced phasic physiological arousal is evoked not only by incorrect responses but also by correct responses and this phasic arousal guides optimal performance on a trial by trail basis during cognitive tasks. Importantly, the effects of these internal signals seem to be independent of valence (see also the reinforcement-learning model of Holroyd and Coles, 2002 for the role of dopaminergic signals to the anterior cingulate cortex depending on performance).…”
Section: Toward An Integrated Approach: Mechanisms Of Cognitive Contr...mentioning
confidence: 99%